Incidencia de la gestión administrativa en la calidad de instrumentos de planificación territorial sostenible del GAD Municipal del cantón Jama-Ecuador - Loor Gómez, Katty Yojanna (2025)
The objective of the study was to evaluate the impact of administrative management on the quality of sustainable territorial planning instruments of the municipal GAD of Jama-Ecuador in three phases: 1) critical process analysis through the review of the PDOT, comparative documentary analysis, and participatory SWOT analysis, 2) evaluation of instruments based on sustainability criteria, and 3) proposal of improvements to optimize administrative management and territorial planning. A total of 376 people participated through a survey comprising 65 questions across 8 dimensions related to sustainable territorial planning. The results showed that the Jama GAD has a robust organizational structure, excelling in citizen participation with 56 assemblies and 690 contributions. However, it faces challenges in financing, monitoring, and economic diversification, reflected in the dissatisfaction of 64% regarding climate actions and 68% concerning road infrastructure maintenance. The PDOT is a solid instrument aligned with the SDGs, but it has areas for improvement in impact monitoring and economic strategies. The statistical evaluation did not find significant associations between variables due to data limitations. In conclusion, while the Jama GAD has made progress in sustainable planning and participatory governance, challenges persist in coordination, resources, and public communication. The improvement plan proposes strategic actions to strengthen administrative management and enhance the quality of sustainable territorial planning instruments.